Application of Shenling lotion in nursing of perineal injury after vaginal delivery (参苓洗液在经阴道分娩产妇产后会阴损伤护理中的应用效果研究) - TANG Yang (唐杨); PENG Hong (彭鸿); WU Qiuxiang (吴秋香); WANG Yan (王燕); WANG Mingyang (王明洋); CHEN Lingfang (陈陵芳) (中西医结合护理)
Objective To investigate the effect of Shenling lotion in nursing of perineal injury after vaginal delivery. Methods A total of 200 puerperal women after vaginal delivery were randomly divided into the control group and observation group, with 100 cases in each group. All puerperal women received routine interventions of perineal care, and those in the observation group were given perineal washing with Shenling lotion. The incidence of vaginal dysbacteriosis, condition of wound healing, pain, perineal edema, comfort of puerperal women, compliance and satisfaction with nursing interventions were compared between two groups. Results All patients recovered with a grade a level of wound healing, and no case of vaginal dysbacteriosis was reported. The Visual Analogue Scale of pain was (1. 66+-0. 76) in the observation group and (2. 00+-0. 68) in the control group, with a significant difference (P＜0. 05). The comfort level of puerperal women in the observation group was higher than that of puerperal women in the control group(P＜0. 05). A higher rate of compliance and satisfaction was reported in the observation group compared with that in the control group. Conclusion perineal washing with Shenling lotion is effective to improve the local peripheral blood circulation, relieve pain, improve comfort of puerperal women and enhanced the quality of perineal care. (目的 探讨参苓洗液在经阴道分娩产妇产后会阴损伤护理中的应用效果。方法 将2022年7月—2024年7月于医院产科住院行经阴道分娩后的200名产妇随机分为对照组和观察组, 各100名。对照组采取常规会阴护理措施, 观察组在对照组基础上采用参苓洗液进行会阴清洗。比较两组阴道菌群失调、伤口愈合、疼痛、会阴水肿、舒适度情况, 观察两组对中医护理操作的依从性和满意度评价。结果 两组产妇阴道分泌物涂片结果显示均未发生菌群失调, 伤口愈合情况均评定为甲级愈合。观察组疼痛评分(1. 66±0. 76)分, 轻于对照组(2. 00±0. 68)分, 差异有统计学意义(P＜0. 05)。观察组舒适度高于对照组 (P＜0. 05)。观察组中医护理操作依从性和满意度均高于对照组。结论 参苓洗液用于清洗经阴道分娩产妇产后会阴伤口, 能促进局部血液循环、缓解疼痛症状, 提高患者的舒适度及满意度, 增强会阴护理效果。)